A unique primary structure of RDL (resistant to dieldrin) confers resistance to GABA‐gated chloride channel blockers in the two‐spotted spider mite Tetranychus urticae Koch. Issue 5 (16th October 2020) - Kobayashi, Takeru; Hiragaki, Susumu; Suzuki, Takeshi; Ochiai, Noriaki; Canlas, Liza J.; Tufail, Muhammad; Hayashi, Naotaka; Mohamed, Ahmed A.M.; Dekeyser, Mark A.; Matsuda, Kazuhiko; Takeda, Makio
Abstract: The primary structure of the second transmembrane (M2) segment of resistant to dieldrin (RDL), an ionotropic γ‐aminobutyric acid receptor (GABAR) subunit, and the structure–function relationships in RDL are well conserved among insect species. An amino acid substitution at the 2′ position in the M2 segment (Ala to Ser or Gly) confers resistance to non‐competitive antagonists (NCAs) of GABARs. Here, a cDNA encoding RDL was cloned from the two‐spotted spider mite Tetranychus urticae Koch. Unlike insect homologs, native Tu RDL has His at the 2′ position (H305) and Ile at 6′ (I309) in the M2 segment and is insensitive to NCAs. Single and multiple mutations were introduced in the M2 segment of Tu RDL, and the mutant proteins were expressed in Xenopus oocytes and examined for the restoration of sensitivity to NCAs. The sensitivity of a double mutant (H305A and I309T in the M2 segment) was greatly increased but was still considerably lower than that of insect RDLs. We therefore constructed chimeric RDLs consisting of Tu RDL and Drosophila melanogaster RDL and examined their sensitivities to NCAs. The results show that the N‐terminal region containing the Cys‐loop as well as the M2 segment confers functional specificity; thus, our current understanding of the mechanism underlying NCA binding to GABARs requires reappraisal. Abstract : The primary structure of the second transmembrane (M2) segment of resistant to dieldrin (RDL), an ionotropic γ‐aminobutyric acid receptor (GABAR) subunit, and the structure–function relationships in RDL are well conserved among insect species. An amino acid substitution at the 2′ position in the M2 segment (Ala to Ser or Gly) confers resistance to non‐competitive antagonists (NCAs) of GABARs. Here, a cDNA encoding RDL was cloned from the two‐spotted spider mite Tetranychus urticae Koch. Single and multiple mutations were introduced in the M2 segment of TuRDL, and the mutant proteins were expressed in Xenopus oocytes and examined for the restoration of sensitivity to NCAs. The sensitivity of a double mutant (H305A and I309T in the M2 segment) was greatly increased but was still considerably lower than that of insect RDLs. We therefore constructed chimeric RDLs consisting of TuRDL and Drosophila melanogaster RDL and examined their sensitivities to NCAs. The results show that the N‐terminal region containing the Cys‐loop as well as the M2 segment confers functional specificity; thus, our current understanding of the mechanism underlying NCA binding to GABARs requires reappraisal.